FBI records : The Vault - USA - Federal Bureau of Investigation (2021)
"The Vault is our new FOIA Library, containing 6,700 documents and other media that have been scanned from paper into digital copies so you can read them in the comfort of your home or office. Included here are many new FBI files that have been released to the public but never added to this website; dozens of records previously posted on our site but removed as requests diminished; files from our previous FOIA Library, and new, previously unreleased files." [self-description]